Optimization of Culture Conditions to Produce Thermostable Keratinolytic Protease of Brevibacillus thermoruber LII, Isolated from the Padang Cermin Hot Spring, Lampung, Indonesia - DEWI SESWITA ZILDA; ENI HARMAYANI; JAKA WIDADA; WIDYA ASMARA; EKO IRIANTO; GINTUNG PATANTIS; YUSRO NURI FAWZYA (Indonesian Society for microbiology, 2012)
Hot springs represent one of the most promising sources for the isolation of thermostable enzyme producers. The microorganisms living in a hot spring not only have to withstand elevated temperatures but also extreme environmental pH and certain chemical compounds that are often toxic to other microbes. A bacterial strain denoted as Brevibacillus thermoruber LII has been isolated from Padang Cermin Hot Spring, Lampung, Indonesia. Optimization of the conditions for protease production by this strain revealed that the isolate produced a thermostable protease optimally at temperature and pH ranges 45-55 C and 6-7, respectively, with keratin as substrate. The strain’s keratinolytic activity was shown by the ability to degrade untreated chicken feathers after 24 h incubation in liquid medium.